MOTIVATING DELEGATION MODEL AND ITS RATIONALE - A. A. Dolgaya (Вестник университета)
The model of motivating delegation has been proposed and its justification by the results of recent studies in educational psychology, neurobiology and pedagogy has been presented. The actualization of the employee’s personal effectiveness lies in his internal, inherent and characteristic motivational model only for him. To build the model, the theory of self-motivation and the phenomenon of self-determination, recent discoveries in neurobiology have been used, a sequence of communication interactions between the director and the employee, which makes it possible to include the motivation of aspiration in the employee’s own motivational model, has been formulated. The main elements of the model are unconscious and conscious desires, and regulatory motives of both the leader and subordinate. Their hierarchy and interaction provide effective employee`s self-motivation in terms of setting the task, developing criteria for assessing the performance of the task. Motivating delegation allows you guaranteed to activate both the emotional part of the performer’s brain, which provides energy for the execution of the task, and the prefrontal complex, which is responsible for the thoughtfulness, creativity and consistency of the result and the process of the performance of the task.